Data-driven forwarding:~a typology of digital platforms for road freight transport management - Christoph Heinbach; Jan Beinke; Friedemann Kammler; Oliver Thomas (Electronic Markets, 2022)
The omnipresence of digital platforms (DPs) across industries yields platform-based business concepts that disrupt the road freight market, enabling the digitalization of road freight transport management (RFTM). However, the data-driven service capabilities of DPs in supporting RFTM are manifold, and platform research provides opportunities to explore the emerging digital business concepts following the core process of transport management systems (TMSs). This, in particular, results from the side of road freight operators engaged in the transport management process that are increasingly forced to provide customer-centric RFTM via DPs to remain profitable and competitive within a fragmented business environment. Against this backdrop, this paper aims to explore DPs in the road freight transport domain to gain insights into digital freight services and support logistics companies involved in the transportation process with a novel navigation for the identification of required platform-based services. Following the grounded theory methodology, we present a morphological box encompassing 14 dimensions and eight DP types aligned to RFTM. We reveal digital services of DP visibility, optimization, and analytics. With the insights obtained by our research, we contribute to developing a comprehensive understanding of DPs for the enhanced decision-making of transport stakeholders in the area of digital transport management. Our findings provide an established theoretical research ground that guides platforms as markets for practitioners and proposes further research avenues for scholars toward data-driven and digitalized transport logistics.
Keywords: O32; 620; Digital platform; Transport management; End-to-end~visibility; Freight forwarding; Data-driven service systems; Smart logistics